Increasing parental knowledge through workshops on early childhood programs, home literacy, and technology use. Issue 4 (2nd October 2019) - Baker, Doris Luft; Ma, Hao; Gallegos, Elisa
ABSTRACT: This experimental study explores the effects of workshops designed to increase directly the knowledge of Latinx parents, and indirectly, their children's vocabulary knowledge. Thirty-two Latinx mothers were randomly assigned to either attend six workshops in Spanish (n = 17), or to a wait-list control group (n = 15). Workshops included carefully designed strategies to scaffold the information based on parent English language proficiency, early childhood knowledge, and technology skills. Results indicate that mothers who attended the workshops significantly increased their early childhood knowledge, and children whose mothers attended the workshops significantly increased their Spanish expressive vocabulary. We did not find significant effects of the workshops on parental technology knowledge and literacy knowledge, although effect sizes were moderate. We discuss our findings in the context of building parental knowledge to increase their role construction and self-efficacy taking their funds of knowledge into account.